L'e-santé en France : déclinaisons et implications territoriales - Joy Raynaud (Netcom)
E-health is synonymous with great promise: improving access, quality, and efficiency of care. After a timid deployment since the 2000s, e-health and, more precisely, telemedicine has vigorously spread during the Covid-19 crisis leading health actors to coordinate and propose innovations in patient care. Health professionals have made massive use of teleconsultation, thus becoming an essential component of the healthcare offer on the territory. Tele-expertise and telemonitoring have also become essential tools for crisis management. Thus, e-health questions the place of the territory in our healthcare system. Telemedicine facilitates access to care but is not a measure for compensating the lack of doctors: territorial anchoring and knowledge of the health and medical-social network are essential. These issues reaffirm the importance of local health governance, which relies on the population and territorial responsibility of health professionals and their coordination ability to meet the health needs of their territory.